Leasing and Insurance Mechanism in Sustainable Agricultural Development - AIMURZINA, Baglan; KAMENOVA, Mazken; OMAROVA, Ainura; SHOKHAN, Roza; KARIPOVA, Ainur; KHOICH, Aizhan (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.v9.6(30).24, 2019)
Economic changes have predetermined public policy, in which its support should play a greater role compared to other sectors. Priority in the development of agricultural production will be indicators of production efficiency, competitiveness of domestic products. In this regard, one of the priorities of the development of the economy of the Republic of Kazakhstan is the accelerated development of the agro-industrial complex on the basis of increasing labour productivity in the agro-industrial sector and increasing exports of processed agricultural products by encouraging a leasing and insurance mechanism. The article analyzes the dynamics of depreciation of fixed assets by type and renewal in agriculture, forestry and fisheries, shows the impact of the formation of mutual insurance on the production efficiency of agricultural producers. The proposals for further improvement of the leasing and insurance mechanisms, including according to the experience of developed countries, are given.